2018 IEEE International Symposium on Power Line Communications and Its Applications (ISPLC) 2018
DOI: 10.1109/isplc.2018.8360242
|View full text |Cite
|
Sign up to set email alerts
|

PAPR reduction of wavelet-OFDM systems using pilot symbols

Abstract: Wavelet transform is at the heart of IEEE 1901 power line communication standard which uses orthogonal frequency-division multiplexing (OFDM) scheme. Examples of wavelets used in designing wavelet-based OFDM (WOFDM) have been shown as possessing lower peak-to-average power ratio (PAPR) than the conventional fast Fourier transform (FFT)-based OFDM. In this study, we investigate 29 different orthogonal wavelets that can be used in designing WOFDM in terms of PAPR and sidelobes behaviour of the filters that enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Further, the orthogonal expression corresponding to the formula (7) is: In general, the MQAM signal constellation is in a rectangular form. For a rectangular signal constellation diagram under 2 k M  ( k is an even number), the MQAM signal constellation is equivalent to two PAM (Pulse Amplitude Modulation) signals on the orthogonal carrier signal [28], [29], [30]. Each of these two signals has 2 2 k M  signal points [31], [32], [33].…”
Section: A Two-dimensional New Communication Technology Working Mechmentioning
confidence: 99%
“…Further, the orthogonal expression corresponding to the formula (7) is: In general, the MQAM signal constellation is in a rectangular form. For a rectangular signal constellation diagram under 2 k M  ( k is an even number), the MQAM signal constellation is equivalent to two PAM (Pulse Amplitude Modulation) signals on the orthogonal carrier signal [28], [29], [30]. Each of these two signals has 2 2 k M  signal points [31], [32], [33].…”
Section: A Two-dimensional New Communication Technology Working Mechmentioning
confidence: 99%
“…where ρ is the attenuation factor that determines the output signal amplitude and d(n) is the distortion noise after F (x(n)) operation. Substituting (16) into (13), gives…”
Section: B Proposed Nonlinear Companding Transformmentioning
confidence: 99%
“…Furthermore, clipping [9]- [11] and companding [12] techniques are applied after OFDM modulation. Other OFDM design kernels such as wavelets [13] possess low PAPR than conventional OFDM scheme. While clipping expands the system processing time due to (2m + 1) fast Fourier transform (FFT)/inverse FFT (IFFT) operations (m is the number of clipping/filtering iterations), companding increases the receiver complexity due to decompanding of companded signals.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative kernel uses the DFT tool except that there exists dilation (stretching) and translation (repositioning) of the signal coefficients. Since WT finds applications in communication systems design, WT-OFDM has been studied by different authors for wireless [13]- [16] and PLC [17], [18] systems. A major drawback in its adoption is that it is computationally inefficient and recent studies have led to different computationally efficient algorithms such as the ones reported in [9] and [19].…”
Section: A Ofdm Systems Design Using Wtmentioning
confidence: 99%